Differences in Iron (Fe) Content in Samples of Refill Drinking Water (AMIU) and Bottled Drinking Water (AMDK) Atomic Absorption Spectrophotometry Method - Indah Sari; Rossa Veronneca; Anita (Jurnal Inspirasi Kesehatan, 2023)
Introduction: Iron is a metal in the first transition Series and the most common element on Earth by mass that makes up most of the outer and inner core of the Earth. High levels of iron (Fe) can be polluted by corrosive gases such as CO2 and H2S. In nature there are various elements that include heavy metals and also a component of pollutants, namely Cd, Hg, Cr, Pb, Ni, Cu, Zn, and Fe. The Aim Of The Research: To determine the difference in iron content in samples of drinking water refills and bottled drinking water Atomic Absorption spectrophotometric method. Research Method: This research was conducted at the mathematics and Natural Sciences Laboratory of Sriwijaya University in January-February 2022 with a total of 20 samples. The Result: The results of the study obtained the average value of iron (Fe) content in refilled drinking water samples 7.7 mg/L and bottled drinking water 3.7 mg/L Atomic Absorption Spectrophotometry method. Mann Witney test obtained the value of p (Sig 2 Tailed) = 0.04. Conclussions: Have different levels of iron in samples of drinking water refills and bottled drinking water Atomic Absorption spectrophotometric method.